2017
DOI: 10.1002/path.4859
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein C‐I plays a role in the pathogenesis of glomerulosclerosis

Abstract: Diabetic nephropathy is the leading cause of end-stage renal disease. Diabetic patients have increased plasma concentrations of apolipoprotein C-I (apoCI), and meta-analyses found that a polymorphism in APOC1 is associated with an increased risk of developing nephropathy. To investigate whether overexpressing apoCI contributes to the development of kidney damage, we studied renal tissue and peritoneal macrophages from APOC1 transgenic (APOC1-tg) mice and wild-type littermates. In addition, we examined renal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 49 publications
(74 reference statements)
3
25
0
Order By: Relevance
“…C5 activation is also observed in patients with lupus nephritis and renal cell carcinoma, which suggests that activated C5 is widespread in kidney diseases (37,38). Since apoCI, encoded by the apoc1 gene, is expressed primarily in the liver, its plasma concentration is associated with an increased risk of developing DN, and it acts as a key factor in the pathogenesis of glomerulosclerosis (39,40). Our results further confirmed that urinary C5 is a specific marker of multiple kidney diseases.…”
Section: Discussionsupporting
confidence: 78%
“…C5 activation is also observed in patients with lupus nephritis and renal cell carcinoma, which suggests that activated C5 is widespread in kidney diseases (37,38). Since apoCI, encoded by the apoc1 gene, is expressed primarily in the liver, its plasma concentration is associated with an increased risk of developing DN, and it acts as a key factor in the pathogenesis of glomerulosclerosis (39,40). Our results further confirmed that urinary C5 is a specific marker of multiple kidney diseases.…”
Section: Discussionsupporting
confidence: 78%
“…In recent years, APOC1 was also reported to play significant roles in some biological processes, such as cholesterol catabolism, dendritic reorganization, and membrane remodeling (6,7). APOC1 is associated with the progression of multiple diseases, including Alzheimer's disease, glomerulosclerosis, type 1 or type 2 diabetes, and diabetic nephropathy (8)(9)(10)(11). Additionally, some studies revealed that APOC1 acts as an oncogene in the progression of some malignant tumors, including breast, pancreatic, colorectal, and lung cancer (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated the anti-inflammatory effects of sFLT-1 on AD in a mouse model. APOC1 transgenic (APOC1-tg) mice develop AD because of a disruption of the skin lipid barrier (Nagelkerken et al, 2008) and a triggered immune system (Bus et al, 2017a). While manifesting many AD hallmarks, the APOC1-tg model does not fully replicate human disease.…”
mentioning
confidence: 99%